2013
DOI: 10.1038/aps.2013.44
|View full text |Cite
|
Sign up to set email alerts
|

Fluopsin C induces oncosis of human breast adenocarcinoma cells

Abstract: Aim: Fluopsin C, an antibiotic isolated from Pseudomonas jinanesis, has shown antitumor effects on several cancer cell lines. In the current study, the oncotic cell death induced by fluopsin C was investigated in human breast adenocarcinoma cells in vitro. Methods: Human breast adenocarcinoma cell lines MCF-7 and MD-MBA-231 were used. The cytotoxicity was evaluated using MTT assay. Time-lapse microscopy and transmission electron microscopy were used to observe the morphological changes. Cell membrane integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…These characteristics of cell death induced by NADA are consistent with typical features of cell death termed oncosis (36,39,40). Like other cases of oncosis (41), cleavage of caspase-3 can be detected in NADA-treated Ba/F3-N cells (Supplementary Fig.…”
Section: Lead Compound Identificationsupporting
confidence: 83%
“…These characteristics of cell death induced by NADA are consistent with typical features of cell death termed oncosis (36,39,40). Like other cases of oncosis (41), cleavage of caspase-3 can be detected in NADA-treated Ba/F3-N cells (Supplementary Fig.…”
Section: Lead Compound Identificationsupporting
confidence: 83%
“…As is known, oncosis is characterized by loss of volume control with massive swelling of most intracellular compartment, often based on ATP deficiency but also related to direct damage to the plasma membrane. It could be quantitated by flow cytometry with PI staining and LDH leakage [6,15,26,27] . Combined with the above result of LDH leakage ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [25] focused on an antibiotic isolated from Pseudomonas jinjuensis , which was previously proved to have anticancer potential, and found that this antibiotic could induce oncosis in breast cancer cells. Steroidal alkaloidal saponins were demonstrated to be natural anticancer agents as they induced apoptosis in cancer cells [26].…”
Section: Discussionmentioning
confidence: 99%